Thoracoscopic Bilateral Bullectomy for Simultaneously Developed Bilateral Primary Spontaneous Pneumothorax: Ipsilateral Transmediastinal versus Bilateral Sequential Approach - Cho, Deog Gon; Lee, Seok In; Chang, Yong Jin; Cho, Kyu Do; Cho, Suk Kyu (The Thoracic and Cardiovascular Surgeon, 2017)
Background Simultaneously developed bilateral primary spontaneous pneumothorax (BPSP) is an indication for thoracic surgery of both sides. Recently, we have reported a new technique for BPSP, which is ipsilateral apicoposterior transmediastinal (TM) bullectomy of both sides using video-assisted thoracoscopic surgery (VATS), and we compared this TM VATS with bilateral sequential (BS) VATS for BPSP.Materials and Methods From June 2003 to May 2014, 11 and 14 patients were performed VATS TM and BS bullectomy for BPSP, respectively. We reviewed the medical records and compared the clinical data between the two groups. For TM group, we first performed the right VATS bullectomy and approached through the apicoposterior mediastinal region for contralateral VATS. In the other group, conventional BS VATS bullectomy was performed in the lateral decubitus position change.Results The mean follow-up was 62.0 ± 32.6 months. No mortality and major complications were observed. The operative time (68.18 ± 24.93 vs. 96.07 ± 37.73, p = 0.046), duration of left pleural drainage (1.00 ± 0.45 vs. 3.21 ± 1.37, p = 0.000), and length of hospital stay (3.82 ± 1.54 vs. 4.93 ± 1.07, p = 0.044) were significantly shorter in the TM group than in the BS group. No significant differences were seen in duration of general anesthesia, total number of wedge resections and endostaplers used in both lungs, duration of right drainage, and postoperative recurrence.Conclusion The TM VATS approach may be a safe and feasible modality for BPSP. It may decrease the operative time, patients inconvenience such as bilateral multiple wounds and longstanding placement of chest tubes, and decrease the hospital stay compared with the BS VATS approach.
Keywords: surgery/incisions; VATS; pneumothorax